Corporate Financial Flexibility, Investment Activities, And Cash Holding: Evidence From Indonesia - Setianto, Rahmat Heru; Kusumaputra, Addenver (UI Scholars Hub, 2017)
This paper examines empirically the impact of financial flexibility on investment activities. Furthermore, we also investigate how financial flexibility determines the sensitivity of investment activities to cash flow. Using annual data of Indonesian manufacturing firms spanning five years, our analyses reveal that financial flexibility enhances investment ability and decreases sensitivity of investment activities to cash flow. Further analysis indicates that financially flexible firms in Indonesia tend to hold higher cash as a buffer to achieve financial flexibility. These findings yield important implications to managers and investors as Indonesia’s domestic market is expanding rapidly and large business opportunities are created. This condition provides firms with incentive to grow faster, hence increasing financing needs to finance firms’ expansion.